Characterisation of III-nitride materials by synchrotron X-ray microdiffraction reciprocal space mapping - Kachkanov, Vyacheslav
X-ray Reciprocal Space Mapping (RSM) is a powerful tool to explore the structure of semiconductor materials. However, conventional lab-based RSMs are usually measured in two dimensions (2D) ignoring the third dimension of diffraction-space volume. We report the use of a combination of X-ray microfocusing and state-of-the-art 2D area detectors to study the full volume of diffraction-space while probing III-nitride materials on the microscale. (C) 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim